Simian Immunodeficiency Virus Infection of Rhesus Macaques Results in Delayed Zika Virus Clearance - Carol L. Vinton (American Society for Microbiology, 2019)
ABSTRACT Flaviviruses are controlled by adaptive immune responses but are exquisitely sensitive to interferon-stimulated genes (ISGs). How coinfections, particularly simian immunodeficiency viruses (SIVs), that induce robust ISG signatures influence flavivirus clearance and pathogenesis is unclear. Here, we studied how Zika virus (ZIKV) infection is modulated in SIV-infected nonhuman primates. We measured ZIKV replication, cellular ZIKV RNA levels, and immune responses in non-SIV-infected and SIV-infected rhesus macaques (RMs), which we infected with ZIKV. Coinfected animals had a 1- to 2-day delay in peak ZIKV viremia, which was 30% of that in non-SIV-infected animals. However, ZIKV viremia was significantly prolonged in SIV-positive (SIV+) RMs. ISG levels at the time of ZIKV infection were predictive for lower ZIKV viremia in the SIV+ RMs, while prolonged ZIKV viremia was associated with muted and delayed adaptive responses in SIV+ RMs. IMPORTANCE Immunocompromised individuals often become symptomatic with infections which are normally fairly asymptomatic in healthy individuals. The particular mechanisms that underlie susceptibility to coinfections in human immunodeficiency virus (HIV)-infected individuals are multifaceted. ZIKV and other flaviviruses are sensitive to neutralizing antibodies, whose production can be limited in HIV-infected individuals but are also sensitive to type I interferons, which are expressed at high levels in HIV-infected individuals. Data in this study highlight how individual components of the innate and adaptive immune responses which become perturbed in HIV-infected individuals influence ZIKV infection.